(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to: "Knowing the objective thinking skills of students of the Department of Mathematics in the faculties of Basic Education." To verify this goal, the following questions must be answered: 1) What is the difference between the arithmetic average and the hypothetical average of the grades of the mathematics department students in the faculties of basic education, the research sample in the objective thinking skills test? 2) What is the difference between the arithmetic average of the scores of the mathematics department students in the faculties of basic education in the research sample in the objective thinking skills test (according to the gender variable)? Where the current research was limited to students of the Department of Mathematics in the faculties of basic education in Iraqi universities. (Morning study), the third stage, for both sexes (males and females), and (360) male and female students were selected, using the stratified random method. It is divided into seven skills, namely: (observation skill, classification skill, comparison skill, interpretation skill, analysis skill, prediction skill, and control skill). The stability of the test was also confirmed using the method of internal consistency coefficient (Alpha - Cronbach), and the reliability coefficient reached (0.802), and the test became composed of (30) paragraphs in its final form, and after applying the search tool to the sample, the test paragraphs were corrected and the data was sorted It was analyzed statistically, and the results of the research showed that there is a difference between the arithmetic mean and the hypothetical average, and it was also found that there is a difference between males and females and in favor of males in objective thinking skills. The most important conclusions: 1) Students of the Mathematics Department in the faculties of Basic Education possess objective thinking skills. 2) There is a difference between the arithmetic average and the hypothetical average of the scores of the mathematics department students in the faculties of basic education in the research sample in the objective thinking skills test. 3) There is a difference between the arithmetic mean of the scores of the mathematics department students in the faculties of basic education in the research sample in the objective thinking skills test (according to the gender variable).